Lisa H. Sideris, Environmental Ethics, Ecological Theology and Natural Selection - Northcott, Michael S. (Journal for the Study of Religion, Nature and Culture, 2005)
Lisa H. Sideris, Environmental Ethics, Ecological Theology and Natural Selection (New York: Columbia University Press, 2003), pp. x + 311. $26.00, ISBN 0-2311-2661-1.